Chemoselective deprotection of N-allylic amines using DDQ - Kumar, Pradeep; Cherian, Shijo K.; Jain, Ruchi; Show, Krishanu (Tetrahedron Letters, 2014)
A highly chemoselective and simple method for the deprotection of N-allylic amines using DDQ has been developed. The use of DDQ in dichloromethane-water provides a mild and efficient one-step deallylation of a wide variety of orthogonally protected tertiary amine derivatives. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Chemoselective deprotection; DDQ; N-Allylic amines; Orthogonally protected tertiary amines